Method Development and Validation of Gas Chromatography-Mass Spectrometry Method for Quantification of Sonidegib in Capsule Dosage Form (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A new simple and precise Gas Chromatography Mass Spectrometry (GC-MS) method was developed and validated for the quantification of sonidegib in capsule formulation. The proposed work is depends on the modification of sonidegib into its derivative with N, O-bis(trimethylsilyl)-trifluoracetamide (BSTFA) with 1% trimethylchlorsilane (TMCS). Selective ion monitoring technique and electron ionization method at 70 eV were utilized for the quantification of sonidegib at m/z 278. Calibration plot was rectilinear in the concentration range of 0.5–10.0 µg/ml. The RSD value for within-day precision was ≤2.47% and for between-day precision was ≤2.45%. The bias value for within-day and between day accuracy was found between -1.51 to 1.87. The intra and inter day recovery findings of sonidegib was found to be between 98.34 to 102.654% for pharmaceutical formulation. The limits of detection and quantification of sonidegib were 0.10 and 0.30µg/ml respectively. No interfering peaks were observed from the excipients of dosage form during the analysis of formulation. The developed procedure was successfully applied for the quantification of commercial sonidegib capsule dosage form to estimate the sonidegib and to check the dosage form uniformity of content.